ARTIFICIAL INTELLIGENCE AS A TOOL TO SERVE HEALTHCARE: LIMITS AND PROSPECTS - BOUCHNITA, Anass; LLORED, Jean-Pierre (MEDECINE LEGALE DROIT MEDICAL, 2025)
Starting from both instances showing how AI is being used in the domain of health and the use of a model designed by ourselves, and following an epistemological line of investigation, we scrutinize the limitations of these new tools and the perspectives they bring for health practitioners.